The Role of Distribution Channels in Improving Marketing Performance and Customer Satisfaction - Wahyu kurniadi (Greenation Management and Business Review, 2025)
This study aims to examine the role of distribution channels in enhancing marketing performance and customer satisfaction. As business competition intensifies, companies must adopt effective distribution strategies to ensure their products are delivered efficiently and reach customers on time. Using a quantitative descriptive method, data were collected through questionnaires distributed to customers and marketing staff. The results indicate that distribution channels have a significant positive impact on both marketing performance and customer satisfaction. Efficient delivery, broad market coverage, product availability, and the use of technology in logistics management contribute to increased sales, better brand perception, and stronger customer loyalty. Furthermore, customer satisfaction is closely linked to the quality of distribution services, including speed, reliability, and ease of access. The study also identifies several challenges, such as delivery delays and limited reach in remote areas. To overcome these challenges, companies are encouraged to invest in digital distribution systems and expand their distribution networks strategically. Overall, the findings underscore that well-managed distribution channels are essential in creating value for customers and achieving competitive advantage in today’s dynamic market environment.